Higgs boson self-coupling at a high-energy γγ collider - Gutiérrez Rodríguez, A. (2011)
We analyzed the double production and the triple self-coupling of the standard model Higgs boson at future γ γ collider energies, with the reactions γ γ → f f H H (f ¯ = b, t). We evaluated the total cross-section for f fHH ¯ and calculated the total number of events considering the complete set of Feynman diagrams at the tree level and for different values of the triple coupling κλHHH . We have also analyzed the sensitivity for the considered reaction and we show the results as 95% CL regions in the κ–MH plane for different values of the center-of-mass energy and different levels of background. The numerical computation was done for the energies which are expected to be available at a possible future linear γ γ collider with a center-of-mass energy 500– 3000 GeV and luminosities of 1 and 5 ab−1. We found that the number of events for the process γ γ → ttHH ¯ , taking into account the decay products of both t and H, is small but enough to obtain information on the triple Higgs boson self-coupling in an independent way, complementing other studies on the triple vertex.